(untitled) (International Journal of Engineering and Computer Science, 2017)
The Internet of Things (IoT) makes brilliant items a definitive building hinders in the improvement of digital physical savvy inescapable systems. The IoT has an assortment of utilization areas, including human services. In the existing system there is no system for analyze step count and medical fitness analysis together. The proposed system is trying to calculate the temperature, blood pressure and heartbeat measurement. In modification part, we include touch sensor based Hardware for measuring step count and calorie burnt in the human body and further blood pressure is measured and updated status to be stored in cloud server. Reminder notification is also included to alert on the phone through messages by using GSM. The system can be used in any big pharma or medical organisation where a large number of patients come, the details of every patient is updated on the web server and the pharma doctor can access the details from anywhere and give the prescription accordingly. The patient also get notification on their mobiles.